Influence of slaughter age and carcass suspension on meat quality in Angus heifers - Ahnström, M. Lundesjö; Hessle, A.; Johansson, L.; Hunt, Melvin C.; Lundström, K. (My University, 2012)
This study investigated the effects of pelvic suspension and slaughter age on longissimus thoracis et lumborum (LTL) from 40 heifers with at least 75% Angus breeding. A total of 20 heifers were slaughtered directly from pasture at 18 months of age, and carcass sides were hung either by the Achilles tendon or the pelvic bone. The other 20 heifers were assigned to an additional winter housing period and slaughtered at 22 months of age; carcass sides were hung only by Achilles suspension. All carcasses were electrically stimulated and assessed according to the EUROP carcass classification system. In addition, the LTL muscles were aged for 7 or 14 days before meat quality was evaluated for intramuscular fat (IMF), drip loss, colour, shear force, compression and sensory analysis. The 22-month-old heifers were heavier, fatter and had more IMF than 18-month-old heifers. Conformation scores (muscling) did not differ between the two slaughter groups. Pelvic suspension reduced both between- and within-animal variation for peak force, total energy and compression peak force. For the 18-month-old heifers, pelvic suspension also decreased peak force, total energy and compression variables for the LTL muscles from both ageing periods, whereas Achilles-suspended samples had lower shear force values only at day 14. Sensory analysis showed that pelvic-suspended sides had greater tenderness, lower bite resistance, less threadiness, higher juiciness and meat flavour and less visible marbling than meat from Achilles-suspended sides. Pelvic-suspended sides at 18 months of age were similar in peak force and total energy values to the 22-month-old heifers. The importance of ageing the Achilles-suspended sides was more obvious for samples from 18-month-old heifers than from the 22-month-old animals. The correlations between the different instrumental measurements and sensory tenderness were considerably higher for carcasses suspended by the Achilles tendon (r = -520.55 to 0.20) than for those hung by the pelvic bone (r = -520.25 to 0.19). More correlations between sensory-evaluated tenderness and shear variables were significant after 7 days (n = 6) of ageing than after 14 days (n = 4) of ageing. This study clearly shows the benefits of pelvic suspension, which reduces the need for additional feeding after pasture.
Keywords: Beef; Pelvic suspension; Tenderness; Shear force; Compression